Determinants of Complete Infant Immunization and Contextual Effect of Community Health Centers: A Multilevel Evidence from Karanganyar, Central Java - Ulfah, Maharani; Respati, Supriyadi Hari; Murti, Bhisma (Journal of Maternal and Child Health, 2020)
Background: Immunization aims to reduce morbidity, mortality, and disability due to vaccine-preventable diseases. Many children in Indo